Metabolic phenotypes and risk of colorectal cancer: a systematic review and meta-analysis of cohort studies - Golnoosh Goodarzi; Hadis Mozaffari; Tahereh Raeisi; Fatemeh Mehravar; Bahman Razi; Maryam Lafzi Ghazi; Nazila Garousi; Shahab Alizadeh; Parisa Janmohammadi (BMC Cancer, 2022)
Abstract Background The association of obesity with colorectal cancer (CRC) may vary depending on metabolic status. Objective This meta-analysis aimed to investigate the combined impacts of obesity and metabolic status on CRC risk. Methods The Scopus, PubMed, and web of sciences databases were systematically searched up to Jun 2021 to find all eligible publications examining CRC risk in individuals with metabolically unhealthy normal-weight (MUHNW), metabolically healthy obesity (MHO), and metabolically unhealthy obesity (MUHO) phenotypes. Results A total of 7 cohort studies with a total of 759,066 participants were included in this meta-analysis. Compared with healthy normal-weight people, MUHNW, MHO, and MUHO individuals indicated an increased risk for CRC with a pooled odds ratio of 1.19 (95% CI = 1.09–1.31) in MUHNW, 1.14 (95% CI = 1.06–1.22) in MHO, and 1.24 (95% CI = 1.19–1.29) in MUHO subjects. When analyses were stratified based on gender, associations remained significant for males. However, the elevated risk of CRC associated with MHO and MUHO was not significant in female participants. Conclusions The individuals with metabolic abnormality, although at a normal weight, have an increased risk for CRC. Moreover, obesity is associated with CRC irrespective of metabolic status.